The INTELed pedagogical framework: Applying embodied digital apps to support special education children in inclusive educational contexts - Martínez-Monés, Alejandra; Villagrá-Sobrino, Sara L.; Georgiou, Yiannis; Ioannou, Andri; Ruiz, María Jiménez (My University, 2019)
The theories of embodied cognition and embodied learning have attracted the attention of researchers and practitioners due to the new possibilities opened up by the emergence of embodied digital learning games. The integration of embodied theories and games to special education has been relatively intense in the last years, but their introduction in inclusive educational contexts is yet scarce. The INTELed project aims at fulfilling this gap, by supporting in-service teachers in acquiring knowledge and skills to use embodied digital learning games to address the needs of special education children in inclusive educational contexts. This paper presents the work conducted at the outset of the INTELed project, aiming at establishing the pedagogical framework with the main components underlying the project.
Keywords: Embodied learning; Inclusive Education; Special Education Needs; Tangible Interfaces; Teacher training